Efficacy of re‐do urethroplasty for post‐traumatic urethral stricture: An analysis of the anatomical and functional outcomes. (19th March 2021) - Tabei, Tadashi; Horiguchi, Akio; Ojima, Kenichiro; Shinchi, Masayuki; Kobayashi, Kazuki; Ito, Keiichi; Azuma, Ryuichi
Abstract : Objectives: To investigate the efficacy of re‐do urethroplasty for post‐traumatic urethral stricture in terms of anatomical and functional outcomes. Methods: A total of 48 patients who underwent re‐do urethroplasty for post‐traumatic urethral stricture due to perineal trauma ( n = 21) and pelvic fracture urethral injury ( n = 27) between October 2010 and March 2020 were retrospectively reviewed. Patients were followed by uroflowmetry, post‐void residual volume assessment and 17‐Fr flexible cystoscopy after re‐do urethroplasty. Successful urethroplasty was defined as having a urethral caliber adequate for the passage of a cystoscope and requiring no additional treatments. Patients completed a validated patient‐reported outcome measure for urethral stricture surgery, including overall satisfaction, and the sexual health inventory for men. Results: The type of re‐do urethroplasty was anastomotic urethroplasty in 45 (94%) patients and buccal mucosa urethroplasty in three (6%) patients. Urethroplasty was successful in 47 (98%) patients (median follow up 35 months, interquartile range 21–75). The patient‐reported outcome measure for urethral stricture surgery and Sexual Health Inventory for Men were assessed in 36 (75%) patients, and the mean lower urinary tract symptom‐specific quality of life, EuroQol‐5D and EuroQol‐visual analog scale scores improved from 2.86, 0.63 and 54.17 preoperatively to 0.78 ( P < 0.001), 0.86 ( P < 0.001) and 76.94 ( P < 0.001) postoperatively, respectively. The pre‐ and postoperative mean Sexual Health Inventory for Men scores (5.92 and 4.94, respectively) did not significantly differ ( P = 0.318). All 36 patients were satisfied with their urethroplasty outcomes, with 20 (56%) very satisfied patients. Conclusions: Re‐do urethroplasty for post‐traumatic urethral stricture shows a high success rate and beneficial effects on both anatomical and functional outcomes.